Exploring Teachers’ Techniques for Introducing English Vocabulary to Young Learners - Dickwan Keumansay; Yuniaria Sika (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
English is the global communication language. It makes English is one of the subjects taught to students from an early age. The introduction of English vocabulary is one of the important materials taught to young learners. At a young age level, learners naturally have the ability to grasp new information quickly but they are still emotionally unstable. They have different characteristics and learning preferences from adults. That’s why teachers must create a suitable learning atmosphere through good and creative teaching techniques so that students are encouraged to be active in the teaching and learning process. Therefore, this article aims to explain some English vocabulary teaching techniques that can be applied by teachers for young learners. The method used is descriptive qualitative research. The researcher interviewed 4 teachers, observed teaching and learning activities in the classroom and conducted a documentation study to collect data. The results showed that there are several techniques used to teach vocabulary to young learners. These techniques are singing, using pictures and drawing, listening and repeating, using real objects, using videos and question and answer.